No color is my kind : Eldrewey Stearns and the desegregation of Houston - Cole, Thomas R., 1949- (University of Texas Press, 2021)
"In 1984, Thomas Cole met Eldrewey Stearns in a Galveston psychiatric hospital. Stearns, a fifty-two-year-old Black man, complained that although he felt very important, no one understood him. Over the course of the next decade, Cole and Stearns, in a tumultuous and often painful collaboration, recovered Stearns's life before his slide into mental illness-as a young boy in Galveston and San Augustine and as a civil rights leader and lawyer who sparked Houston's desegregation movement between 1959 and 1963"-- Provided by publisher.
Description based upon print version of record.
Keywords: Stearns, Eldrewey.; Cole, Thomas R., -- 1949-; Stearns, Eldrewey; Civil rights movements -- Texas -- Houston -- History -- 20th century.; African American civil rights workers -- Texas -- Houston -- Biography.; Civil rights workers -- Texas -- Houston -- Biography.; Mentally ill -- Texas -- Houston -- Biography.; Houston (Tex.) -- Race relations.; Mouvements des droits de l'homme -- Texas -- Houston -- Histoire -- 20e siècle.; Défenseurs des droits de l'homme noirs américains -- Texas -- Houston -- Biographies.; Défenseurs des droits de l'homme -- Texas -- Houston -- Biographies.; Personnes vivant avec un trouble de santé mentale -- Texas -- Houston -- Biographies.; BIOGRAPHY & AUTOBIOGRAPHY / Cultural Heritage; African American civil rights workers; Civil rights movements; Civil rights workers; Mentally ill; Race relations; Texas -- Houston; 1900-1999; Houston, mental illness, desegregation, Texas history, race in America, civil rights movement, civil rights leader, desegregation movement, bipolar disorder, civil rights.; Biographies; History